1991
DOI: 10.1073/pnas.88.19.8840
|View full text |Cite
|
Sign up to set email alerts
|

Functional heterogeneity of mutant rhodopsins responsible for autosomal dominant retinitis pigmentosa.

Abstract: Thirteen mutant rhodopsins responsible for autosomal dominant retinitis pigmentosa (ADRP) have been produced by transfection of cloned cDNA into tissue culture cells. Three mutants [class I: Phe45 --Leu, termination (deletion of C-terminal positions 344-348), and Pro-347 --Leul resemble wild-type rhodopsin in yield, regenerability with 11-cis-retinal, and plasma membrane localization. Ten mutants Met, His, Thr-58 --Arg, Val-87 -* Asp, Gly-89 Asp, Gly-106 -Trp, Arg-135 --Leu, Arg-135 Trp, Tyr-178 -+ Cys, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
271
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(288 citation statements)
references
References 23 publications
16
271
1
Order By: Relevance
“…Glycosylation of asparagine (Asn-15) requires the amino acid sequence Asn-Xaa-(Ser or Thr), where Xaa is any amino acid except proline. Sung et al (1991b) supported this assignment. In transfection of cloned c D N A into tissue culture cells, Thr-17-Met mutation produces only the 31-kDa and 35-kDa protein which appeared to be degraded with no higher molecular mass species observed.…”
Section: Discussionsupporting
confidence: 54%
“…Glycosylation of asparagine (Asn-15) requires the amino acid sequence Asn-Xaa-(Ser or Thr), where Xaa is any amino acid except proline. Sung et al (1991b) supported this assignment. In transfection of cloned c D N A into tissue culture cells, Thr-17-Met mutation produces only the 31-kDa and 35-kDa protein which appeared to be degraded with no higher molecular mass species observed.…”
Section: Discussionsupporting
confidence: 54%
“…Now, more than 26 different kinds of single-base mutations and a few cases of deletion of codon (s) within the coding region of rhodopsin gene have been identified in ADRP patients (Inglehearn et al, 1991;Keens et al, 1991 ;Sung et al, 1991a;Dryja et al, 1991, etc.). Moreover, it has been identified that at least two distinct biochemical defects have been associated with different rhodopsin mutants in ADRP (Sung et al, 1991b). Therefore, these allelic heterogeneities suggest a clinical variability.…”
Section: Discussionmentioning
confidence: 99%
“…We also included two positive controls: P23H, the most common pathogenic mutation in rhodopsin, 4,9,10 where there is clear evidence of pathogenicity using in vitro expression systems and immunocytochemistry, [11][12][13][14][15] and ∆68-71, which spans one of our variants and has been demonstrated to be functionally inactive. [16][17][18] spectrophotometry WT and variant constructs were transiently transfected into human embryonic kidney cells (Supplementary Materials and Methods online).…”
Section: Construct Generationmentioning
confidence: 99%